NLRP3 Inhibition Leads to Impaired Mucosal Fibroblast Function in Patients with Inflammatory Bowel Diseases - Weber, Simone; Sitte, Selina; Vögele, Anna-Lena; Sologub, Ludmilla; Wilfer, Angelika; Rath, Timo; Nägel, Andreas; Zundler, Sebastian; Franchi, Luigi; Opipari, Anthony W.; Sonnewald, Sophia; Reid, Stephen; et al. (Journal of Crohns & Colitis, 2023)
Background and Aims: Inflammatory bowel diseases (IBD) are characterized by mucosal inflammation and sequential fibrosis formation, but the exact role of the hyperactive NLRP3 inflammasome in these processes is unclear. Thus, we studied the expression and function of the NLRP3 inflammasome in the context of inflammation and fibrosis in IBD. Methods: We analysed intestinal NLRP3 expression in mucosal immune cells and fibroblasts from IBD patients and NLRP3-associated gene expression via single-cell RNA sequencing and microarray analyses. Furthermore, cytokine secretion of NLRP3 inhibitor treated blood and mucosal cells, as well as proliferation, collagen production, and cell death of NLRP3 inhibitor treated intestinal fibroblasts from IBD patients were studied. Results: We found increased NLRP3 expression in the inflamed mucosa of IBD patients and NLRP3 inhibition led to reduced IL-1β and IL-18 production in blood cells and diminished the bioactive form of mucosal IL-1β. Single cell analysis identified overlapping expression patterns of NLRP3 and IL-1β in classically activated intestinal macrophages and we also detected NLRP3 expression in CD163+ macrophages. In addition, NLRP3 expression was also found in intestinal fibroblasts from IBD patients. Inhibition of NLRP3 led to reduced proliferation of intestinal fibroblasts, which was associated with a marked decrease in production of collagen type I and type VI in IBD patients. Moreover, NLRP3 inhibition in intestinal fibroblasts induced autophagy, a cellular process involved in collagen degradation. Conclusions: In the presented study, we demonstrate that inhibiting NLRP3 might pave the way for novel therapeutic approaches in IBD, especially to prevent the severe complication of intestinal fibrosis formation.
CRIS-Team Scopus Importer:2023-11-17
Keywords: fibroblasts; fibrosis; IL-18; IL-1β; Inflammatory bowel diseases; mucosal immune system; NLRP3 inflammasome; small molecule inhibitor